ANALISIS KEGIATAN PRAKTIKUM BIOLOGI KELAS X DAN XI SMAN 10 PADANG TAHUN PELAJARAN 2012/2013 - Anggriyani, Ria; Lufri, Lufri; Zulyusri, Zulyusri (Kolaboratif, 2013)
Discovery process (scientific work) in biology learning in the form of lab activity is necessary to strengthen the studentâ€™s understanding of concepts. This study aims to determine the quality of the biology lab activities (planning, implementation process and evaluation), problems of biology lab activity and causes of failure in biology lab activities class X and XI SMAN 10 Padang in second semesterÂ academic year 2012/2013. This research is a descriptive study combining data collection techniques quantitatively and qualitatively. Data of planning obtained from lesson plan (RPP) assessment sheet and interview guide. Data of implementation process obtained from the observation sheet, record product and field notes. Data of practicum evaluation obtained from the interview guide. Data of practicum problems which includes problems faced by teacher obtained from the teacher questionnaire and interview guide, the problems faced by students obtained from student questionnaire and interview guide and the problems. Causes of failure in lab activities data obtained from the interview guide. Based on this research can be concluded about the quality of planning, categorized as medium in terms of suitability of lesson plan with School Based Curricullum, there are teachers who did not prepare lesson plan and practicum guide and did not plan practicum in accordance with the demands of School Based Curricullum. Implementation process on teacher performance aspects categorized as medium, on student activities categorized as good and readiness of facilities and infrastructure aspects categorized as very good. Practicum evaluation is not based on School Based Curricullum. In doing practicum, biology teachers less constrained at planning, quite constrained at the practicum process and evaluation, while students who followed the practicum is quite constrained in the planning, practicum process and evaluation of the practicum. Cause of failure in lab activities is lack of ability in allocating the time to do practicum in accordance with the demands of School Based Curricullum.